2022
DOI: 10.1155/2022/4539367
|View full text |Cite|
|
Sign up to set email alerts
|

Inter-Relationship Between a Transcriptional Regulator of Flagella Genes cj0440c and Thiamine Metabolic Pathway in Campylobacter jejuni

Abstract: Campylobacter jejuni is a major cause of gastroenteritis in humans. It has been reported that the pathogenesis of C. jejuni is closely related to the formation, adhesion, and invasion of flagella toxin in host epithelial cells. A putative transcriptional regulator, known as cj0440c, is thought to be involved in the regulation of flagellar synthesis. However, confirmation of this hypothesis requires deep insight into the regulation mechanism of cj0440c and its possible relationship with different antibiotics. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Manipulated or compromised peer review …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Manipulated or compromised peer review …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%